1994
DOI: 10.3109/02713689409015091
|View full text |Cite
|
Sign up to set email alerts
|

TGF-β1 induces lens cells to accumulate α-smooth muscle actin, a marker for subcapsular cataracts

Abstract: Spindle-shaped myofibroblast-like cells, which contain alpha-smooth muscle actin, have been described in anterior subcapsular cataract and after-cataract. In a previous study in this laboratory, it was shown that transforming growth factor-beta (TGF beta) induces the formation of spindle-shaped cells in lens epithelial explants. The aim of this investigation was to determine whether these TGF beta-induced spindle-shaped cells contain alpha-smooth muscle actin. Lens epithelial explants were prepared from 21-day… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
76
0

Year Published

1999
1999
2017
2017

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 150 publications
(79 citation statements)
references
References 15 publications
3
76
0
Order By: Relevance
“…α-SMA is a well known marker of myofibroblast-like cells, and accumulates in tissues characterized by fibrosis or anterior subcapsular cataract, but not in normal tissue [8,28,39,42]. Therefore, in order to examine the role of MMP-2 in the expression of α-SMA, we performed a Western blot analysis.…”
Section: Overexpression Of Mmp-2 Induces Transformation Of Lecsmentioning
confidence: 99%
See 2 more Smart Citations
“…α-SMA is a well known marker of myofibroblast-like cells, and accumulates in tissues characterized by fibrosis or anterior subcapsular cataract, but not in normal tissue [8,28,39,42]. Therefore, in order to examine the role of MMP-2 in the expression of α-SMA, we performed a Western blot analysis.…”
Section: Overexpression Of Mmp-2 Induces Transformation Of Lecsmentioning
confidence: 99%
“…α-SMA is used as a marker for transformed fibrotic cell types in various tissues [30,[36][37][38][39], and is also observed in LECs in pathological conditions [8,40]. Therefore we examined immunoreactivity for α-SMA and MMP-2 in rat lenses incubated with TGF-β " .…”
Section: Presence Of Mmp-2 Within the Anterior Subcapsular Plaques Ofmentioning
confidence: 99%
See 1 more Smart Citation
“…Numerous studies have shown that inappropriate TGFβ signaling in the eye results in an EMT that bears a morphologic and molecular resemblance to some forms of human cataract, including anterior subcapsular cataract (ASC) and posterior capsular opacification (PCO; 56). Reports of increased levels of TGFβ in many eye diseases (57), together with other studies in vitro and in vivo, have shown that TGFβ-induced EMT of lens epithelial cells results in human ASC phenotypes (57,(58)(59)(60)(61)(62)(63)(64). All report the presence of elongate, spindle-shaped myofibroblastlike cells, as well as lens capsule wrinkling, apoptotic cell death and extensive accumulation of ECM, interspersed between the transdifferentiated cells.…”
Section: Introductionmentioning
confidence: 99%
“…In a recent study, TSA was found to suppress proliferation and EMT of lens epithelial cells (LECs) using SRA01/04 and HLEB3 lines. 20 As transdifferentiated LECs show increased expression of αSMA, a marker for subcapsular cataracts and PCO, 3,4,21,22 the current study was designed to study the effect of histone acetylation by TSA on αSMA and the changes that take place at its promoter region during TGF-β-induced EMT of LECs.…”
Section: Introductionmentioning
confidence: 99%